Developing social indicators for the evaluation of natural resource management programmes using a capability approach in the Eastern Cape, South Africa - Human, Johanna Susanna (Rhodes University, Faculty of Education, Department of Education, 2020)
The dissertation investigates how the capability approach can be used to develop social indicators for a natural resource management (NRM) programme. The study aimed to develop an understanding of what the beneficiaries of the programme value being and doing to guide the development of social indicators that will take into consideration their personal development aspirations. These valued beings and doings were then overlaid with the programme goals and objectives to identify and select the final indicators. The study was situated in the Tsitsa catchment in the Eastern Cape, South Africa and was part of a natural resource management programme, focused on land restoration and avoided degradation. Methods used to collect data for this study and develop an understanding of what the residents' valued beings and doings were, included semi-structured interviews, workshops and document analysis. The research population was non-homogenous. I tried to include voices representing different prominent groups of land users in the study. This included established commercial farmers, emerging commercial farmers, commercial forestry, residents residing in communal areas and engaged with subsistence farming and residents from these communal areas who are now residing elsewhere but continue to have connections to the catchment. Understanding the voices of these different groups who reside in the catchment was important to develop an inclusive understanding of what residents of the catchment valued beings and doings were. The research process was supported by participatory approaches. This process, and the lessons learnt during the research process, were valuable for the further development and implementation of the planned participatory monitoring evaluation reflection and learning (PMERL) framework. The research process involved learning from the research participants about their valued beings and doings and what was important for the programme implementers. Some of the research participants from the Rhodes University implementation team (RUIT) were also involved in selecting the indicators they thought the programme should monitor. Overall, using the capability approach helped me to gain insight and understanding with regard to what the valued beings and doings are for the residents of the catchment and what they would like development programmes, such as the Tsitsa Project, to address. It was surprising to find many areas of overlap between the valued beings and doings of the different residents in the catchment, as well as the similarities between these and the goals and objectives of the Tsitsa Project. In conclusion, using the capability approach was useful to learn what was important for the residents of the catchment to help develop the social indicators but also to learn how to guide and steer participatory monitoring and evaluation processes in the future.
Keywords: Environmental education -- South Africa -- Eastern Cape; Natural resources -- Management -- Study and teaching (Continuing education) -- South Africa -- Eastern Cape; Sustainable development -- Study and teaching (Continuing education) -- South Africa -- Eastern Cape; Environmental economics -- Study and teaching (Continuing education) -- South Africa -- Eastern Cape; Subsistence farming -- South Africa -- Eastern Cape; Watersheds -- South Africa -- Eastern Cape; Capabilities approach (Social sciences); Tsitsa River Catchment (Eastern Cape, -- South Africa)